Stung by Pension Reforms: The Impact of a Change in State Pension Age on Mental Health and Life Satisfaction of Affected Women - Marina Della Giusta; Simonetta Longhi (Institute of Labor Economics (IZA), 2020)
Several reforms increased the state pension age (SPA) in the UK and equalised it to age 65 for both men and women. We use panel data and a difference-in-difference approach to comprehensively analyse the direct and indirect effects of these reforms, investigating mechanisms for indirect effects. We also analyse the heterogeneity of the effects of smaller versus larger increases in SPA, by partnership status, as well as spill-over effects to male partners. Consistent with previous research, we find a positive impact of the reform on employment and labour force participation, but also large negative impacts on various aspects of personal, financial, and mental wellbeing. The effect is larger for women who have to wait longer to reach their SPA, and smaller for women with a partner (compared to those without a partner). The effect of the reform partially spills over to affected women partner's labour market participation. Our results can be generalised to other countries that are seeking to implement similar reforms.
Keywords: I31; J22; J26; 330; policy reform; retirement; labour supply; care supply; leisure; wellbeing